Review on Realization of AES 256bit Encryption with Raspberry Pi - Erick Fernando; Surjandy Surjandy; Muhamad Irsan; Hetty Rohayani A H; Fachruddin Fachruddin (Universitas Multimedia Nusantara, 2019)
In this article, it aims to present the AES encryption on the Raspberry Pi mini pc. this application also aims to illustrate that this AES algorithm can be applied with small resources. This research was conducted with an experimental approach, which carried out the implementation process in mini pc hardware and xampp software (php, apache). This AES algorithm is tested by PHP programming with Apache web server with text data. The results of the study, that the AES algorithm can run well with a hard minimum, like raspberry mini pc with a very fast time in the process, speed in the process and a lot of text data. So, AES algorithm can be widely adopted for various applications from raspberry PI mini pc computers with strong practicality in information security and reliability.